2005
DOI: 10.1002/bdd.466
|View full text |Cite
|
Sign up to set email alerts
|

Fate of tritiated didemnin B in mice: excretion and tissue concentrations after an intraperitoneal dose

Abstract: Didemnin B has undergone trials in cancer patients, and has antiviral and immunosuppressive properties. [(3)H]didemnin B was administered intraperitoneally (i.p.) to mice at 320 or 1280 microg/kg. Urine and feces were collected until 168 h, at which time the mice were killed and tissues collected. Additionally, [(3)H]didemnin B was given i.p. at 320 microg/kg, and mice were killed at 1-120 h post-dosing. Radiolabel increased rapidly in blood then rapidly declined. Most radiolabel in urine, feces and tissues re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The terminal half-life of HHT has been determined to be 14.4 hrs in human [54] and 40.6 hrs in dogs [55]. The clearance of Did B from the blood of human patients is biphasic with apparent half-lives of 0.12 and 4.8 hrs [56] and its observed terminal half-life in mice is 16.2 hrs [57]. The elimination half-life of Bru in mice has been estimated to be greater than 12 hrs and in human serum it is biphasic and progresses through an initial fast half-life of 15 min followed by a second half-life of 0.7–13.8 hrs depending on the patients [58].…”
Section: Discussionmentioning
confidence: 99%
“…The terminal half-life of HHT has been determined to be 14.4 hrs in human [54] and 40.6 hrs in dogs [55]. The clearance of Did B from the blood of human patients is biphasic with apparent half-lives of 0.12 and 4.8 hrs [56] and its observed terminal half-life in mice is 16.2 hrs [57]. The elimination half-life of Bru in mice has been estimated to be greater than 12 hrs and in human serum it is biphasic and progresses through an initial fast half-life of 15 min followed by a second half-life of 0.7–13.8 hrs depending on the patients [58].…”
Section: Discussionmentioning
confidence: 99%
“…administration (Beasley et al. ), we examined gross pancreatic and islet morphology by insulin staining and light microscopy (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…delivery (Beasley et al. ). Both the intestine and pancreas are known sites of production of the orexigenic peptide, ghrelin, with the intestine being the more important source in mice (Wierup et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beasley and colleagues (45) completed a study of the excretion and tissue concentrations of [ 3 H] didemnin B in mice after intraperitoneal administration. Interestingly, they found that the pancreas had the greatest concentration of radiolabel at both the high and low doses 7 days after administration, which suggested possible efficacy in animal models for the treatment of pancreatic cancer.…”
Section: -6 Antitumour Pharmacology Of Marine Natural Products Wimentioning
confidence: 99%